2020
DOI: 10.1088/2051-672x/abb294
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ZrO2 nanoparticle reinforced Ni–W, Ni–B and Ni–Cu matrix nanocomposites

Abstract: In this work, the structure and properties of ZrO2 nanoparticle reinforced Ni–W, Ni–B and Ni–Cu matrix nanocomposite coatings were comparatively studied. Their surface morphology, composition, microstructure, topography, hardness, wear and corrosion resistance were examined by various methods . The nanocomposites exhibit dense, nodular-like morphology with nanocrystalline structure. The results show that the ZrO2 particles have homogeneously dispersed in the nanocomposites. The formation of the protrusion stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The XRD patterns depicted that the HVOF method can effectively limit the generation of decarburization phases because of the high velocity and relatively low temperature of the flame. The increase in the formation of non-crystalline amorphous phases occurs due to very fast cooling during the spraying process [33]. Stewart et al demonstrated that the presence of different phases and their proportion mostly depends on the process conditions when depositing the coating powder on the base material [34].…”
Section: Energy Kevmentioning
confidence: 99%
“…The XRD patterns depicted that the HVOF method can effectively limit the generation of decarburization phases because of the high velocity and relatively low temperature of the flame. The increase in the formation of non-crystalline amorphous phases occurs due to very fast cooling during the spraying process [33]. Stewart et al demonstrated that the presence of different phases and their proportion mostly depends on the process conditions when depositing the coating powder on the base material [34].…”
Section: Energy Kevmentioning
confidence: 99%
“…Until recently, the urgent demand for high-performance materials has forced researchers to conduct more research on Ni-B coatings. A number of studies have reported that the incorporation of various micro- and nanoparticles such as Al 2 O 3 [ 12 ], SiC [ 13 , 14 ], ZrO 2 [ 15 , 16 ], TiN [ 17 , 18 ], AlN [ 19 , 20 ], TiO 2 [ 21 ], and diamond [ 22 ] within the Ni-B matrix can further enhance the mechanical and anti-corrosion properties, among others. The embedding of these solid particles in a Ni-B alloy coating provides longer-lasting and effective protection for the surfaces of various mechanical components working in extreme environments such as high-load, high-temperature, or corrosive environments.…”
Section: Introductionmentioning
confidence: 99%